2012
DOI: 10.1016/j.jcin.2012.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Coronary Reactivity Testing in Women With No Obstructive Coronary Artery Disease

Abstract: Objective We evaluated the safety of coronary reactivity testing (CRT) in symptomatic women with evidence of myocardial ischemia and no obstructive coronary artery disease (CAD). Background Microvascular coronary dysfunction (MCD) in women with no obstructive CAD portends an adverse prognosis of 2.5% annual major adverse cardiovascular event (MACE) rate. The diagnosis of MCD is established by invasive CRT, yet the risk of CRT is unknown. Methods We evaluated 293 symptomatic women with ischemia and no obstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
63
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 184 publications
(63 citation statements)
references
References 40 publications
0
63
0
Order By: Relevance
“…154, 155 An annual major adverse cardiovascular event rate of 2.5% is present in women with CMD and risk factors for CMD have not been fully elucidated. 156 CMD is characterized by a decrease in the size of epicardial vessels and microvasculature, diffuse atherosclerotic disease, increased arterial stiffness and fibrosis, altered remodeling, and the presence of endothelial or smooth muscle dysfunction. 157 The microcirculation cannot be investigated by angiogram, thus, several techniques for functional assessment, of coronary flow reserve (non-invasive and invasive) have evolved, however the gold standard is an invasive coronary reactivity test.…”
Section: Ischemic Heart Disease In Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…154, 155 An annual major adverse cardiovascular event rate of 2.5% is present in women with CMD and risk factors for CMD have not been fully elucidated. 156 CMD is characterized by a decrease in the size of epicardial vessels and microvasculature, diffuse atherosclerotic disease, increased arterial stiffness and fibrosis, altered remodeling, and the presence of endothelial or smooth muscle dysfunction. 157 The microcirculation cannot be investigated by angiogram, thus, several techniques for functional assessment, of coronary flow reserve (non-invasive and invasive) have evolved, however the gold standard is an invasive coronary reactivity test.…”
Section: Ischemic Heart Disease In Womenmentioning
confidence: 99%
“…The WISE study highlighted the importance of CMD in women 141 and supported the use of invasive coronary vasomotor testing as a safe method for definitive diagnosis and assessment of prognosis in high-risk women. 156 Early detection of endothelial dysfunction, measured by brachial artery flow-mediated vasodilation, has also been associated with a substantial increase in IHD in women. 158 Additional simpler noninvasive techniques have emerged, with specially designed fingertip probes to measure the peripheral reactive hyperemia index, a measure thought to reflect endothelial function.…”
Section: Ischemic Heart Disease In Womenmentioning
confidence: 99%
“…The change in coronary diameter in response to high dose ACH was significantly different between the two groups (p = 0.013) (Table 2). There was no coronary artery spasm noted to highest dose of ACH in this protocol (36.4 µg) , with coronary artery spasm defined as >70% vasoconstriction (7). …”
mentioning
confidence: 87%
“…Study was IRB approved and all participants gave written informed consent. Participants underwent clinically indicated CRT via a highly standardized protocol as previously published (7), with Doppler tipped guidewire (Flowire®,Volcano) placed in the left anterior descending coronary artery. Bolus injections of intracoronary adenosine (18 µg, 18 µg and 36 µg) were used to determine coronary flow reserve (CFR).…”
mentioning
confidence: 99%
“…[16] While CRT has been shown to be safe [16] it is time consuming and requires an experienced interventionist with advanced training to perform, and therefor is not routinely available. Studies have demonstrated that cardiac magnetic resonance imaging (CMRI) with myocardial perfusion imaging has been shown to be predictive of death, MI, hospitalization for worsening angina in women with CMD.…”
Section: Introductionmentioning
confidence: 99%